Writing history in Renaissance Italy - Ianziti, Gary (Harvard Univ. Press, 2012)
Bruni on writing history – The Plutarchan option – A new life of Cicero – Between Livy and Polybius: Bruni on the first Punic War – Genesis of the Florentine histories – The Florentine histories: a sourcebook for statesmen – Bruni and biography: a life of Aristotle – Parallel lives: Dante and Petrarch – Bruni, the Medici, and the Florentine histories – The Florentine histories: from policy to propaganda – A distant mirror: Athens, Sparta, and Thebes – Memoirs of a humanist – Writing from Procopius
2011017920
Keywords: Bruni; Leonardo; Historians; Biographers; Humanists; Historiography; Renaissance